2019
DOI: 10.12691/ajnr-7-4-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foot Reflexology on Physiological Indicators and Mechanical Ventilation Weaning Time among Open-Heart Surgery Patients

Abstract: Shortening the length of mechanical ventilation (MV) and lowering dose of sedatives among critically ill patients can decrease complications, intensive care length of stay and mortality rate. Therefore, introducing non-pharmacologic interventions such as reflexology became an issue of concern for critical care nurses. The purpose of this study was to investigate the effect of foot reflexology on physiological indicators and mechanical ventilation weaning time in open-heart surgery (OHS) patients. Methods: Quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
0
0
Order By: Relevance
“…The results also showed that foot reflexology caused significant changes in the physiological indices of HR and blood pressure. The results of the present study are consistent with those of previous studies on children with leukemia [19] and adults undergoing open-heart surgery [27], those with bronchoscopy [28], and in the intensive care unit [29]. The high impact of foot reflexology can be attributed to the presence of many nerves in the foot.…”
Section: Discussionsupporting
confidence: 92%
“…The results also showed that foot reflexology caused significant changes in the physiological indices of HR and blood pressure. The results of the present study are consistent with those of previous studies on children with leukemia [19] and adults undergoing open-heart surgery [27], those with bronchoscopy [28], and in the intensive care unit [29]. The high impact of foot reflexology can be attributed to the presence of many nerves in the foot.…”
Section: Discussionsupporting
confidence: 92%
“…Applying the reflexology technique causes relaxation for the nervous system and calmness effect. Massaging reflexology areas of the lung on the foot positively influence pulmonary function which in turn reduces ventilation dependence (Elsayed et al, 2019). The current study was in the same line with the findings of Polat & Ergüney, 2016;Miller, et al, 2016) who concluded that massaging the heart reflex point increases the blood supply to the heart which enables the heart to pump the oxygen-rich blood around the body and improves oxygenation.…”
Section: Discussionsupporting
confidence: 90%
“…However, the exact point of the massage and physiological pathways in the human body remains unclear [18]. Further studies are necessary to obtain a shred of stronger scientific evidence to support foot massage interventions and enrich knowledge in this field [19]. Hence, this study was conducted to explore the effect of foot massage on pain levels among postoperative CABG patients.…”
Section: Complementary and Alternative Therapymentioning
confidence: 99%